2021
DOI: 10.1186/s12950-020-00266-0
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone can attenuate the pulmonary inflammatory response via regulation of the lncH19/miR-324-3p cascade

Abstract: Objective To investigate lncRNAs and their roles in regulating the pulmonary inflammatory response under dexamethasone (Dex) treatment. Methods IL-1β (10 ng/mL) and LPS (1 μg/mL) was used to construct inflammatory cell models with A549 cells; IL-1β performed better against LPS. Different concentrations of Dex were used to attenuate the inflammation induced by IL-1β, and its effect was assessed via RT-PCR to detect inflammatory cytokine-related mRNA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Moreover, previous studies have revealed IL-17 as a cytokine involved in chronic inflammatory neurological diseases, and we can confirm that, in our neuronal model, it can be modulated from the inflammation [52,53]. All these data are relevant for the proper understanding of cytokines signaling pathways involved in the regulation of neuroinflammation and could be crucial for the development of new therapeutical strategies [54].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, previous studies have revealed IL-17 as a cytokine involved in chronic inflammatory neurological diseases, and we can confirm that, in our neuronal model, it can be modulated from the inflammation [52,53]. All these data are relevant for the proper understanding of cytokines signaling pathways involved in the regulation of neuroinflammation and could be crucial for the development of new therapeutical strategies [54].…”
Section: Discussionsupporting
confidence: 82%
“…Dexamethasone, a synthetic glucocorticoid, induces anti-inflammatory effects through inhibition of the NF-κΒ signalling pathway (Chen et al. 2021 ). Dexamethasone has been commonly used as a positive control in inflammation-related studies (Huang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Results presented herein, although limited, suggest that the effect of drugs such as dexamethasone should be better studied in vitro by using physiomimetic models like the ones developed in the present work. Studies with dexamethasone-treated epithelial cells in much more responsive 2D models showed a decrease in the proinflammatory cytokines ( Chen et al, 2021 ; Patil et al, 2018 ), but the results presented in this work are the first ones conducted in a 3D model with more physiological responsiveness to the LPS hit. Regarding MSCs, results are more controversial: while some in vitro studies have shown a decrease in cytokines and chemokines secreted by cytokine-stimulated LMSCs under dexamethasone effects ( Wallace et al, 2001 ; Kim, Cheng, and Kim 1999 ), in vivo studies point that dexamethasone could be abrogating the anti-inflammatory effect of MSC ( Chen et al, 2014 ; Wang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 67%